Voice of the nurse in paediatric intensive care: a scoping review - Denise Alexander; Maria Brenner; Michael Connolly; Kate Masterson (BMJ Open)
Objectives The objective was to explore how the voice of the nurse in paediatric intensive care units (PICU) is portrayed in the literature.Design Scoping review using the six-step scoping review framework outlined by Arksey and O’Malley.Data sources PubMed, Nursing (OVID), Medline (OVID), CINHAL (EBSCO), SCOPUS and Web of Science online databases. The initial search was conducted in June 2020 and was repeated in January 2023.Eligibility criteria The review included publications in English; published since 2010 in peer-reviewed journals; papers identified nurses in the population studied and conducted in PICU.Data extraction and synthesis The papers were screened by abstract and subsequently by reading the full text by two independent reviewers. The literature was imported into the software program NVivo V.12 for thematic analysis.Results The scoping review identified 53 articles for inclusion. While the value of seeking the voice of the nurse has been identified explicitly in other healthcare contexts, it has only been identified indirectly in PICU. Four main themes emerged from the data: the voice of the nurse in the organisation of PICU, caring for children in PICU, as a healthcare professional, and communication in PICU.Conclusion While this literature suggests many facets of the complex role of the nurse, including partnership with families and advocating for patients, the limited literature on care delivery reduces the capacity to fully understand the voice of the nurse at key junctions of care. Further research is needed on the voice of the nurse in PICU to illuminate the barriers and enablers for nurses using their voices during decision-making.